2003
DOI: 10.1002/ajh.10382
|View full text |Cite
|
Sign up to set email alerts
|

Immune thrombocytopenic purpura associated with Brucella and Toxoplasma infections

Abstract: Bacterial and protozoal infections can cause thrombocytopenia and may mimic idiopathic thrombocytopenic purpura (ITP). Brucella species and Toxoplasma are among the infectious agents with protean clinical manifestations which may induce immune thrombocytopenia. In rare cases, thrombocytopenia can be severe and may result bleeding into the skin and from mucosal sites. Prompt recognition of this complication and aggressive therapy are essential, since the mortality associated with bleeding into the central nervo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 8 publications
(11 reference statements)
0
18
0
Order By: Relevance
“…Immune-mediated thrombocytopenia may also occur during the course of brucellosis [6] And an inflammatory process occurs in brucellosiscausing increase in acute phase reactants [29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune-mediated thrombocytopenia may also occur during the course of brucellosis [6] And an inflammatory process occurs in brucellosiscausing increase in acute phase reactants [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Isolated thrombocytopenia (platelets <150x109/L) was seen in 8% of cases in a study reported from Turkey [6]. Immune-mediated thrombocytopenia may also occur during the course of brucellosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thrombocytopenia related to systemic infections may be due to a variety of causes: hypersplenism, bone marrow suppression, disseminated intravascular coagulation, increased clearance, immune-mediated destruction, hemophagocytosis, and adherence to damaged vascular surfaces [4][5][6][7][8][9][10]. The data is presently insufficient regarding the management of Brucella-associated bleeding and the time for antimicrobial therapy to take effect [10,11]. In this report, we discuss the management of a Turkish patient with brucellosis who presented with bleeding as the first manifestation of illness due to severe thrombocytopenia.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombocytopenia, reported in 1-26% of cases, can cause bleeding in only very rare cases [1][2][3]. Thrombocytopenia related to systemic infections may be due to a variety of causes: hypersplenism, bone marrow suppression, disseminated intravascular coagulation, increased clearance, immune-mediated destruction, hemophagocytosis, and adherence to damaged vascular surfaces [4][5][6][7][8][9][10]. The data is presently insufficient regarding the management of Brucella-associated bleeding and the time for antimicrobial therapy to take effect [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Immune-mediated thrombocytopenia is a clinically important mechanism that may be encountered during the course of brucellosis (11,12). Brucella-associated thrombocytopenia can be associated with hypersplenism, autoimmune destruction due to the development of antithrombocyte antibodies, disseminated intravascular coagulopathy (DIC), hemophagocytosis and granulomas in bone marrow (6,9,11,13,14).…”
Section: Discussionmentioning
confidence: 99%